2004
DOI: 10.1096/fj.04-1614fje
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of defective sarcoplasmic reticulum Ca2+transport in diabetic heart of transgenic rats expressing the human kallikrein‐1 gene

Abstract: The bradykinin-forming enzyme kallikrein-1 is expressed in the heart. To examine whether contractile performance and sarcoplasmic reticulum Ca2+ transport of the diabetic heart can be rescued by targeting the kallikrein-kinin system, we studied left ventricular function and sarcoplasmic reticular Ca2+ uptake after induction of streptozotocin-induced diabetes mellitus in transgenic rats expressing the human tissue kallikrein-1 gene. Six weeks after a single injection of either streptozotocin (70 mg/kg ip) or ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
18
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 48 publications
(84 reference statements)
4
18
1
Order By: Relevance
“…Diabetic cardiomyopathy is a distinct entity independent of coronary artery disease and commonly prevalent in the diabetic population (2). Pathophysiology of diabetic cardiomyopathy include, for example, microangiopathy, endothelial dysfunction, cardiac fibrosis, and disruption of the intracellular Ca 2ϩ transport, all triggered by the diabetic milieu (3)(4)(5). Additionally, inflammation with increased numbers of immunocompetent cells in the cardiac tissue plays a pivotal role in the pathophysiology of diabetic cardiomyopathy, as we were able to demonstrate recently in an experimental model of diabetes (6,7).…”
supporting
confidence: 54%
See 2 more Smart Citations
“…Diabetic cardiomyopathy is a distinct entity independent of coronary artery disease and commonly prevalent in the diabetic population (2). Pathophysiology of diabetic cardiomyopathy include, for example, microangiopathy, endothelial dysfunction, cardiac fibrosis, and disruption of the intracellular Ca 2ϩ transport, all triggered by the diabetic milieu (3)(4)(5). Additionally, inflammation with increased numbers of immunocompetent cells in the cardiac tissue plays a pivotal role in the pathophysiology of diabetic cardiomyopathy, as we were able to demonstrate recently in an experimental model of diabetes (6,7).…”
supporting
confidence: 54%
“…Diabetic cardiomyopathy is associated with left ventricular dysfunction (3,4,7,20). We recently showed that increased cytokine levels in the cardiac tissue correlate with the degree of cardiac failure in experimental diabetes (6), a finding that may explain their multiple cardiodepressive effects (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These abnormalities include, among others, cardiac fibrosis [5] and cardiac inflammation, which lead to left ventricular (LV) dysfunction, mediated mainly by the diabetic milieu (e.g. high glucose levels, oxidative stress, angiotensin II) [2,4,6]. Cardiac inflammation, not only in diabetic cardiomyopathy, but also in most kinds of heart failure, is accompanied by elevated cardiac protein levels of cytokines, such as TNF-α, IL1-β, IL6, and TGF-β1.…”
Section: Introductionmentioning
confidence: 99%
“…Diverse pathologic mechanisms, including microangiopathy, myocardial fibrosis, interstitial inflammation, oxidative damage, and abnormalities in calcium homeostasis, are known to contribute for the development of DMCMP. [4][5][6][7][8][9] As a consequence of above pathologic mechanism, functionally, diastolic and systolic functions of ventricle are impaired, 10)11) and subsequent structural changes are responsible for increased myocardial fibrosis and stiffness. 1)12) After far-advanced structural changes, the impairment of damaged myocardial function may be irreversible.…”
mentioning
confidence: 99%